2015
DOI: 10.1021/acs.jafc.5b03557
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Allergenic Potential of Transgenic Wheat (Triticum aestivum) with Reduced Levels of ω5-Gliadins, the Major Sensitizing Allergen in Wheat-Dependent Exercise-Induced Anaphylaxis

Abstract: The ω5-gliadins are the major sensitizing allergens in wheat-dependent exercise-induced anaphylaxis (WDEIA). In this study, two-dimensional immunoblot analysis was used to assess the allergenic potential of two transgenic wheat lines in which ω5-gliadin genes were silenced by RNA interference. Sera from 7 of 11 WDEIA patients showed greatly reduced levels of immunoglobulin E (IgE) reactivity to ω5-gliadins in both transgenic lines. However, these sera also showed low levels of reactivity to other gluten protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Since the omega-5 gliadins are the major sensitizing proteins in the serious food allergy WDEIA, the immunogenic potential of DH20 was evaluated by 2-D immunoblot analysis using sera from patients with verified cases of WDEIA. Patient sera were characterized previously by ELISA using individual gluten protein fractions and by 2D immunoblot analysis [ 16 ]. In the two parental lines, proteins identified as omega-5 gliadins showed the greatest amounts of IgE reactivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the omega-5 gliadins are the major sensitizing proteins in the serious food allergy WDEIA, the immunogenic potential of DH20 was evaluated by 2-D immunoblot analysis using sera from patients with verified cases of WDEIA. Patient sera were characterized previously by ELISA using individual gluten protein fractions and by 2D immunoblot analysis [ 16 ]. In the two parental lines, proteins identified as omega-5 gliadins showed the greatest amounts of IgE reactivity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in ω-gliadin expression observed between the old and the modern groups of durum wheat genotypes are of great interest in relation to the potential allergenicity of pasta wheat. In a recent study with transgenic bread wheat in which ω-5 gliadin genes were silenced by RNA interference (Altenbach et al, 2015), reduced binding was observed with sera from allergic patients. It may therefore be possible to exploit variation in wheat germplasm to produce cultivars with reduced amounts of ω-5 gliadins.…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore be possible to exploit variation in wheat germplasm to produce cultivars with reduced amounts of ω-5 gliadins. It is known that ω-gliadin expression is highly affected by the environment (Hurkman et al, 2013, Wan et al, 2014, Altenbach et al, 2015). Our study showed that ω-gliadin expression was generally higher in 2013, also characterised by lower rainfall during grain filling.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven wheat (species: Triticum aestivum ; order: poales ) allergens are listed so far in the WHO/IUIS Allergen Nomenclature database ( www.allergen.org ) starting with the wheat profilin (Tri a 12) up to Tri a 45, an elongation factor 1. Tri a 19 (omega-5-gliadin), a 65-kDa seed storage protein, is the best-characterized single wheat component and is involved in wheat-dependent, exercise-induced anaphylaxis (WDEIA) and also for the early childhood type-I wheat allergy [ 18 ••, 34 ]. Tri a 19 is commercially available as a single allergen component but is not relevant for the diagnosis of baker’s asthma [ 35 •].…”
Section: Cerealsmentioning
confidence: 99%